The Cais das Artes cultural complex: “suspended” museum - Mendes, Neusa Maria (Farol, 2024)
This article makes considerations about Cais das Artes, located in the city of Vitória, Espírito Santo, Brazil, and which has been under construction since 2007, and the National Coach Museum (2008-2016) in Lisbon, Portugal. Both projects were designed by the award-winning Espírito Santo architect Paulo Mendes da Rocha. The research seeks to highlight the practice of architecture and proposes an investigation into museums as the main focus. Therefore, the text tries to emphasize the statement to the praxis, even though the Cais das Artes is, today, a monument to ruin. These two cultural facilities, with very similar characteristics and located in areas marked by port dynamics, which give an extraordinary dimension to the place, encourage a dialogical reading in which, in my opinion, the social, museological and cultural fields meet. Therefore, I seek to demonstrate the social place of the museum, based on the sociomuseology school of thought, centered on architecture, which amalgamates what is effectively in dispute: museum, city and society.